Strategy, control and competitive advantage : Case study evidence - Nilsson, Fredrik; Rapp, Birger; Jannesson, Erik (Management for Professionals, 2014)
How should firms' control systems be designed and used to formulate and implement strategies that will contribute to competitive advantage and sustained high performance? This book offers some thought-provoking suggestions.   It contains empirical studies of such diverse manufacturing enterprises as Atlas Copco, Electrolux, Saab, Scania, SCA Packing and Volvo, as well as an insurance company and two chamber orchestras. All firms and organizations presented offer interesting and exciting insights, each in a specific way and each with a fascinating history. The book presents research on the relationship between strategy, control and competitive advantage over extended periods and at several strategic levels, while also taking into account the existence of multiple control systems in a single firm or other organization. Readers are offered an in-depth look into how changes in the environment lead to adjustments in strategies and control systems. It is shown, in addition, how difficult and challenging it can be to implement these changes, and why such efforts are not always successful. But perhaps most importantly, the book conveys an in-depth understanding of how strategies and control systems affect competitive advantage and performance. In both its coverage and focus, the book is unique. Not only does it provide valuable contributions to the research field of strategy and management control; it also represents a substantial commitment in terms of resources and involvement over an extended period. The book is highly recommended to researchers, practitioners, graduate students and all others interested in this area.